Model Kolaborasi Pembelajaran Riset Rekonstruksi Sarana Dan Prasarana Berbasis Smart Settlement Untuk Mitigasi Bencana Banjir Pada Program MBKM Jalur Proyek Kemanusiaan - Naidah Naing (Universitas Muslim Indonesia, 2022)
MBKM research activity This humanitarian project will examine the collaboration between the community and students in implementing the design of a Smart Settlement-based facility and infrastructure reconstruction model that can mitigate flood disasters in Salomenraleng sub-district, Wajo Regency. The flood disaster which every year hits residential areas in Salomenraleng Village, causes settlement facilities and infrastructure to not function properly. As a result, the quality of settlements and the environment decreases as the population cannot access facilities and infrastructure in the event of a flood. For this reason, a model for the reconstruction of facilities and infrastructure based on smart settlement is needed in mitigating flood disasters in this area. The purpose of this study is to prepare excellent students who can apply the design of a smart settlement-based model of reconstruction of residential facilities and infrastructure that mitigates flood disasters in assisting the community in overcoming flood problems to uphold human values, in the village of Salomenraleng. The target of this humanitarian project research is the collaboration of students, lecturers, the community, and the government. Where students and lecturers are the implementers of activities, the community is the object of the disaster and the government is the policymaker. The method used in this research is the total sampling method (population), with the Parties Involved: (1) Students assisted by lecturers (2) the Community, and (3) Wajo Regency Government. The research output is a National Journal Draft with ISSN, the results of the formulation of flood disaster mitigation policies, and data collection on facilities and infrastructure based on intelligent settlements.